2006
DOI: 10.1103/physrevb.74.195342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wetting-layer wave functions on phonon-mediated carrier capture into self-assembled quantum dots

Abstract: Models of carrier dynamics in quantum dots rely strongly on adequate descriptions of the carrier wave functions. In this work we numerically solve the one-band effective mass Schrödinger equation to calculate the capture times of phonon-mediated carrier capture into self-assembled quantum dots. Comparing with results obtained using approximate carrier wave functions, we demonstrate that the capture times are strongly influenced by properties of the wetting layer wave functions not accounted for by earlier theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
2
12
2
Order By: Relevance
“…Moreover, the capture time defined as τ = R 1/ has the same order of magnitude as that obtained by Magnusdottir et al without taking into account the phonon confinement [23]. It is seen that there exist bands of dot radii where capture is energetically allowed, in accordance with previous results [23,29]. This means that the appearance of these bands is not caused with phonon confinement.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the capture time defined as τ = R 1/ has the same order of magnitude as that obtained by Magnusdottir et al without taking into account the phonon confinement [23]. It is seen that there exist bands of dot radii where capture is energetically allowed, in accordance with previous results [23,29]. This means that the appearance of these bands is not caused with phonon confinement.…”
Section: Resultssupporting
confidence: 86%
“…It should be noted that in the capture rate dependence appear 7 and 4 bands for LO1-and IO-phonon coupling cases, respectively, when the QD radius changes from a 0.3 B to a 2 B . In addition, in contrast to previous results [23,29], which obtained without taking into account the phonon confinement, we found that the height of the peaks is lowered as QD radius decreases. It is natural to assume that this is due to spatial confinement of the phonon modes as the latter leads to a strong dependence of the electron-phonon interaction Hamiltonian on the QD radius.…”
Section: Resultscontrasting
confidence: 83%
“…Furthermore, we employ here a two-band description of the QD including the effects of a wetting layer and strain, which is sufficient to capture the essential properties of QDs. 33,34 The envelope function approach we use here is valid even for QD sizes as small as an atomic unit cell because the small effective masses and shallow confinement potentials in this system ensure that the envelope functions are slowly varying on the atomic scale even if the confinement potential is not. 35 The inclusion of more bands is important for studying excited states of quantum dots, but for ground-state transitions the effects are small.…”
Section: Theoretical Description Of Spontaneous Emission From Quamentioning
confidence: 99%
“…1. Notice that the model assumes local equilibrium between QD and wetting layer states, 9 which is consistent if the capture time, usually on the order of a few picoseconds or less, 10 is smaller than the inverse of the modulation frequency predicted by the model. Furthermore, scattering rates need to be low enough, a͒ Electronic mail: suhr@fotonik.dtu.dk.…”
Section: ͑3͒mentioning
confidence: 91%